Isolasi dan identifikasi senyawa steroid daun beluntas (Pluchea indica L.) menggunakan metode kromatografi kolom - Puri, Ananda Anggelita Aprina (Maliki Interdisciplinary Journal, 2024)
Beluntas leaf (Pluchea indica L.) is a hedge plant that grows wild in yards. Beluntas leaves contain active compounds such as steroids. The purpose of the study was to isolate steroid compounds using the sonication method, determine the results of separation using column chromatography and identification using UV-Vis. Beluntas leaves are extracted by sonication using ethanol solvent then hydrolyzed with HCl, partition with chloroform solvent. Phytochemicals are added Liebermann-Burchard reagents. The extract results were separated by column chromatography and KLTA. Characterization using a UV-Vis spectrophotometer. The results of the study obtained a crude extract yield of 24.85%, a partition yield of 7.05%. Positive phytochemical tests of steroids color to green, blue, there are rings. Separation using column chromatography obtained eluents of 80 vials, KLTA monitoring obtained parallel stains on vials 28, 32, 36, 40 and 44, Rf value 0.46. UV-Vis characterization obtained a conjugated wavelength of 274.9 nm (C=C).